2013
DOI: 10.1073/pnas.1303888110
|View full text |Cite
|
Sign up to set email alerts
|

Mass spectrometry reveals synergistic effects of nucleotides, lipids, and drugs binding to a multidrug resistance efflux pump

Abstract: Multidrug resistance is a serious barrier to successful treatment of many human diseases, including cancer, wherein chemotherapeutics are exported from target cells by membrane-embedded pumps. The most prevalent of these pumps, the ATP-Binding Cassette transporter P-glycoprotein (P-gp), consists of two homologous halves each comprising one nucleotide-binding domain and six transmembrane helices. The transmembrane region encapsulates a hydrophobic cavity, accessed by portals in the membrane, that binds cytotoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
158
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 162 publications
(173 citation statements)
references
References 47 publications
13
158
0
2
Order By: Relevance
“…Previous studies on the N TAIL -P XD complex by small-angle X-ray scattering (SAXS) and NMR showed that the majority of N TAIL remains disordered in the bound state, thus supporting the fuzzy and heterogeneous nature of this complex [33,38,44]. Although hydrophobic complexes could be expected to dissociate in the gas phase, detection of such complexes by MS has been reported in some instances [45][46][47]. The results of this study show that the MeV N TAIL -P XD complex is amenable to MS analysis and that distinct conformational states can be detected.…”
Section: Introductionmentioning
confidence: 90%
“…Previous studies on the N TAIL -P XD complex by small-angle X-ray scattering (SAXS) and NMR showed that the majority of N TAIL remains disordered in the bound state, thus supporting the fuzzy and heterogeneous nature of this complex [33,38,44]. Although hydrophobic complexes could be expected to dissociate in the gas phase, detection of such complexes by MS has been reported in some instances [45][46][47]. The results of this study show that the MeV N TAIL -P XD complex is amenable to MS analysis and that distinct conformational states can be detected.…”
Section: Introductionmentioning
confidence: 90%
“…This proof copy is the copyright property of the publisher and is confidential until formal publication. mass spectrometry as demonstrated by Marcoux et al (2013). They used purified mouse Abcb1 in a detergent (n-dodecyl-ÎČ-D-maltoside-DDM) containing buffer and analyzed direct lipid binding to Abcb1 and then determined the bound lipids by mass spectrometry.…”
Section: Article In Pressmentioning
confidence: 99%
“…They used purified mouse Abcb1 in a detergent (n-dodecyl-ÎČ-D-maltoside-DDM) containing buffer and analyzed direct lipid binding to Abcb1 and then determined the bound lipids by mass spectrometry. In this study, three cardiolipin molecules were found bound to the substrate-binding cavity of Abcb1, and by related calculations, the size and number of lipids present simultaneously in the substrate-binding pocket were also determined (Marcoux et al, 2013). As a further expansion of this study, Marcoux et al performed molecular docking in which they showed that cardiolipin-14 binds to K230 and K822 found in transmembrane helices TM4 and 9 previously shown to be involved in lipid sensing (see Section 4.1.1).…”
Section: Article In Pressmentioning
confidence: 99%
See 1 more Smart Citation
“…However, electron density in the low resolution electron cryo-microscopy single particle reconstruction envelope of TmrAB was assigned to the detergent micelle (9). In the low resolution crystal structure of the eukaryotic P-glycoprotein, no lipids were observed (10,11), but non-denaturing mass spectrometry identified tightly associated lipids and a clear dependence of ligand and lipid binding (12).…”
mentioning
confidence: 99%